2007
DOI: 10.1093/cvr/cvm008
|View full text |Cite
|
Sign up to set email alerts
|

 -adrenergic relaxation in pulmonary arteries: preservation of the endothelial nitric oxide-dependent  2 component in pulmonary hypertension

Abstract: beta1- and beta2-AR, but not beta3-AR, mediate relaxation of mice pulmonary arteries. The beta2-AR component is dependent on eNOS activity and is preserved following chronic hypoxia. These data highlight the role of the beta2-AR as a pharmacological target to induce/restore endothelial NO-dependent protective effects in pulmonary circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 37 publications
7
46
0
Order By: Relevance
“…Endothelial β 2 -AR stimulation elicits a NO-dependent relaxant response in both systemic [7][8][9] and pulmonary [6] vasculature. However, the molecular mechanisms involved in the coupling of β 2 -ARs to eNOS activation remained poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Endothelial β 2 -AR stimulation elicits a NO-dependent relaxant response in both systemic [7][8][9] and pulmonary [6] vasculature. However, the molecular mechanisms involved in the coupling of β 2 -ARs to eNOS activation remained poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we have shown that in mouse pulmonary artery precontracted by PGF 2α , 0.1 µM procaterol (in the presence of phentolamine) induces a relaxation which is exclusively due to the endothelial β 2 -AR, eNOS and soluble guanylyl-cyclase stimulation [6].…”
Section: Role Of G I/o Proteins In the β 2 -Ar-mediated Relaxant Respmentioning
confidence: 93%
See 3 more Smart Citations